Analysis Of the Effect of Financial Ratios and Operating Expenses on The Profitability of Islamic Banks with Non-Performing Financing (NPF) As A Moderating Variable - Lukman Nurjati; Anton Bawono (Lembaga Bale Literasi, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO) on profitability proxied by Return on Assets (ROA) with Non Performing Financing (NPF) as a moderating variable in Islamic Commercial Banks in Indonesia during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from the annual financial reports of Islamic Commercial Banks and the Islamic Banking Statistics published by the Financial Services Authority (OJK). The research sample consists of 12 Islamic Commercial Banks selected using purposive sampling, resulting in 60 observations during the research period. The analytical method used is panel data regression with Moderated Regression Analysis (MRA) to examine the influence of independent variables and the role of the moderating variable. The results show that CAR and FDR have a positive and significant effect on ROA, while BOPO has a negative and significant effect on ROA, and NPF has a positive and significant effect on ROA. Furthermore, the moderation analysis indicates that NPF weakens the influence of CAR and FDR on ROA while strengthening the effect of BOPO on ROA. These findings indicate that the management of capital adequacy, liquidity, operational efficiency, and financing quality plays an important role in improving the profitability of Islamic Commercial Banks in a sustainable manner.